Model-informed drug development of novel ROCK2 inhibitor TDI01: population pharmacokinetic study and simulation - Ji, Xiwei; Cui, Yimin (Frontiers in Pharmacology, 2025)
IntroductionTDI01 is a novel and highly selective ROCK2 inhibitor, which provides a potential valuable candidate for the treatment of ALI/ARDS due to COVID-19.MethodsThe objective of this study was to develop Pop-PK models to characterize the PK properties of TDI, and to guide the choice of suitable clinical dosage regimens via model-based simulation.ResultsThe completed clinical study suggested a double peak phenomenon, which could be observed after single administration of TDI01. Thus, a one-compartment model with dosage effect and hepato-enteral circulation were developed to describe the PK profiles of TDI01 in vivo. Results from the simulation show that the drug accumulation observed after multiple doses would not affect the safety of TID01 usage under the tested dosage regimen.Discussion The established model and simulation provide a useful approach to maximize the clinical medication safety and therapeutic efficacy of TDI01.